The generalized two-photon excitation cross-section of Xe revisited. Issue 14 (January 2020) - Blondel, C; Alkhoury, J; Jannaud, T; Drag, C
Synopsis: Two-photon absorption laser-induced fluorescence (TALIF) is a technique commonly used for density and/or temperature diagnostics, mainly of oxygen atoms, in flames and plasmas. Usually, density measure-ments are based on the comparison with the signal obtained, at a similar wavelength, in pure xenon. The cross-section of xenon thus appears a key parameter, the measure of which has not been consolidated by independent measurements. The present experiment is a direct measurement of this two-photon cross-section.